Role of the education assistant in inclusive school: actions from a systematic vision. Construct by Taeho Psychoeducational Organization in the framework of the project “Escuela de Brazos Abiertos” - Martínez, Mayluc (2018)
In the present dissertation, we analyze the vision about education assistants to inclusive school, also called, in diverse latitudes, teaching assistants or teacher’s aides, although not indistinctly. In this regard, we started with a documentary research, where a number of documents were reviewed (articles, research, essays, papers, degree theses and master’s theses, including legal and regulatory documents), which referred to this professional, in order to understand how it is defined, what their profile, their role or their duties within the educational organization are and how they are linked or should be linked with the other participants in the process. We have tried to limit the revision to a Hispanic and/or Ibero-American context, and to works published over the last ten years. After that, we have made a syncretism, a construct, that allows us to look into the duties of the education assistant within the inclusive school. In this regard, we have proposed 8 categories of action, according to the Index for Inclusion, which we developed based on duties ranging from support in the diagnosis and the project of educational center transformation to behavioral care, contributing to a discipline based onmutual respect. In the middle of these, thinking about other categories such as respect for diversity and heterogeneity inside and outside the classroom, planning, student activities and tasks, participation and collaborative learning, work networks and shared resources, and evaluation. It is important to note that this work is part of a larger study, which is related to an experience that has taken place over the last two years: the project named “Escuela de Brazos Abiertos”, where educational institutions of the city of Valencia, Venezuela, participate. The project seeks to analyze and understand ways to collaborate in the process of institutional transformation towards an inclusive education, from a systemic approach,considered as a complex phenomenon where there is an interaction, not only among the students, but the other participants, systems and subsystems: families, the school as an institution, teachers, the curricula, institutions that provide psychoeducational and therapeutic services, and the one that focuses this work on: education assistants of the inclusive school.